Latent Social Capital in the Marpege-Pege Wedding Tradition - Nurhalimah Nasution; Syafwan Rozi; Penmardianto (BELIEF: Sociology of Religion Journal, 2025)
This research explores the Marpege-pege tradition in traditional Angkola Batak weddings as a social mechanism that addresses the high costs of marriage, especially the bridewealth obligation (tuhor). Conducted in Sialogo Village, West Angkola District, South Tapanuli Regency, the study focuses on (1) how the Marpege-pege tradition is practiced and (2) its role in the community. Employing a qualitative descriptive approach and Robert K. Merton’s structural functionalism framework, data were gathered through observations, in-depth interviews, and documentation with community members. Results reveal that Marpege-pege is a coordinated collective effort of monetary contributions organized by the groom’s family, involving stages: Manyapai Boru, Marpege-pege, and Pataru Tuhor. From a functionalist view, this tradition has an obvious role in easing wedding expenses. Additionally, it fosters latent functions like enhanced social solidarity, stronger community bonds, and the preservation of cultural values across generations. These latent functions bolster social capital by supporting reciprocal relationships and collective responsibility within the community. The study concludes that Marpege-pege is more than just an economic tactic; it is a culturally embedded tradition that sustains social cohesion and cultural continuity in Angkola Batak society.